Magnetohydrodynamic effects on liquid metal flows in an open channel for fusion plasma facing components with a transverse magnetic field - Jun-Hua Pan; Ming-Jiu Ni (Nuclear Fusion)
Laminar magnetohydrodynamics film flows in an open channel of arbitrary electrical conductivity under the influence of a transverse magnetic field are investigated. The effects of the magnetic field, channel conductivity, and channel width on current and velocity distributions are discussed. The present research establishes quantitative scaling law for the magnetic field’s impact on the film thickness, utilizing Fourier eigenfunction series and comprehensive physical modeling. The scaling law is validated through direct numerical simulation results and experimental data, which accounts for factors that influence the film thickness, including the Reynolds number (volume flow rate), channel inclined angle, and magnetic field strength. Additionally, the physical mechanism governing the three-dimensional evolution of magnetohydrodynamics films is explored, which finds that a strong magnetic field introduces a Lorentz separation eddy and destabilizes the initially stable, flat film. The present investigations will contribute to the design of flowing liquid metal plasma facing components in tokamak fusion reactors.